Effectiveness Of Self-Instructional Module On Knowledge Regarding Lifestyle Modification To Maintain A Healthy Heart Among Cad Patients Admitted In Selected Hospital Of The City - Tumbare, Nikhil Rohidas; Kolapkar, Pallavi Shekhar; Bhusal, Rahul Chimaji; Prabhakar Korde, Rajkannya; Vetal, Dattatray Namdev (Journal of Neonatal Surgery, 2025)
Introduction: Cardiovascular disease is a main cause of mortality and disability in spite of extensive hard work to manage cardiac risk factors in the course of diet, exercise, and medications (Roger, et al 2012). Cardiovascular disease (CVD) comprises all diseases of the circulatory system, cerebro- vascular disease, hypertension, peripheral arterial disease, rheumatic heart disease, congenital disease, heart failure, deep vein thrombosis and pulmonary embolism and coronary heart disease (Go, et al, 2014). Coronary artery disease (CAD), as well referred to as coronary heart disease (CHD), is the tapering of the small blood vessels that deliver blood and oxygen to the heart (United States National Library of Medicine, 2016). Coronary artery disease (CAD) incorporates acute myocardial infarction, other acute ischemic heart disease, angina pectoris, atherosclerotic cardiovascular disease, and all other types of chronic ischemic coronary heart disease Objectives: The objective of this study was to evaluate the effectiveness self instructional module on knowledge regarding lifestyle modification to maintain healthy heart among CAD patient admitted in selected hospital. 1. To assess the knowledge regarding knowledge regarding lifestyle modification to maintain healthy heart among CAD patient admitted in selected hospital. 2. To assess effectiveness of self instructional module on knowledge regarding lifestyle modification to maintain healthy heart among CAD patient admitted in selected hospital. 3. To find association between pre-test knowledge score with their selected demographic variables. Methods: Quasi experimental one group pre test post test design was used to assess " effectiveness self instructional module on knowledge regarding lifestyle modification to maintain healthy heart among CAD patient admitted in selected hospital " is the main goal of the current study. Sample size was 100 CAD patient admitted in selected hospital by using nonprobability purposive sampling technique. Results: The study reveals that majority 62% of the participants had poor knowledge in pretest and in post test 72% had average knowledge. Result shows that self instructional module is effective in improving knowledge regarding lifestyle modification to maintain health heart among CAD patient. difference of level of knowledge regarding lifestyle modification to maintain health heart among CAD patient post test and pre test mean score found 17.38 and 10 respectively and paired t test value was found to be 15.43 which is significant at the level of 0.05. The findings revealed that their was significant association between Knowledge score and socio demographic variables like Age and awareness about lifestyle modification. Conclusion: The findings of the present study indicated regarding effectiveness of Self Instructional Module on knowledge regarding lifestyle modification to maintain health heart among CAD patient, shows that the CAD patient had good knowledge in posttest. it shows that Self Instructional Module is effective in improving knowledge regarding lifestyle modification to maintain health heart among CAD patient